Identification of Genes that Elicit Disuse Muscle Atrophy via the Transcription Factors p50 and Bcl-3 - Wu, Chia-Ling; Kandarian, Susan C.; Jackman, Robert W. (PloS one, 2011)
Skeletal muscle atrophy is a debilitating condition associated with weakness, fatigue, and reduced functional capacity. Nuclear factor-kappaB (NF-κB) transcription factors play a critical role in atrophy. Knockout of genes encoding p50 or the NF-κB co-transactivator, Bcl-3, abolish disuse atrophy and thus they are NF-κB factors required for disuse atrophy. We do not know however, the genes targeted by NF-κB that produce the atrophied phenotype. Here we identify the genes required to produce disuse atrophy using gene expression profiling in wild type compared to Nfkb1 (gene encodes p50) and Bcl-3 deficient mice. There were 185 and 240 genes upregulated in wild type mice due to unloading, that were not upregulated in Nfkb1⁻/⁻ and Bcl-3⁻/⁻ mice, respectively, and so these genes were considered direct or indirect targets of p50 and Bcl-3. All of the p50 gene targets were contained in the Bcl-3 gene target list. Most genes were involved with protein degradation, signaling, translation, transcription, and transport. To identify direct targets of p50 and Bcl-3 we performed chromatin immunoprecipitation of selected genes previously shown to have roles in atrophy. Trim63 (MuRF1), Fbxo32 (MAFbx), Ubc, Ctsl, Runx1, Tnfrsf12a (Tweak receptor), and Cxcl10 (IP-10) showed increased Bcl-3 binding to κB sites in unloaded muscle and thus were direct targets of Bcl-3. p50 binding to the same sites on these genes either did not change or increased, supporting the idea of p50:Bcl-3 binding complexes. p65 binding to κB sites showed decreased or no binding to these genes with unloading. Fbxo9, Psma6, Psmc4, Psmg4, Foxo3, Ankrd1 (CARP), and Eif4ebp1 did not show changes in p65, p50, or Bcl-3 binding to κB sites, and so were considered indirect targets of p50 and Bcl-3. This work represents the first study to use a global approach to identify genes required to produce the atrophied phenotype with disuse.